Action learning and action research to alleviate poverty. (2nd January 2020) - Boak, George; Gold, Jeff; Devins, David
ABSTRACT: The purpose of this paper is to examine the role played by action learning in a collaborative action research project to alleviate poverty in a city region in the UK. Researchers from two universities worked with 12 large anchor organisations to investigate procurement and employment practices that positively impacted inclusive growth within the city region, and therefore had a positive effect on poverty, and spread those practices more widely. A core group of representatives from the 12 participating organisations met in action learning sets to share the results of their investigations, to design a model of good practice, and to develop and support action plans. The paper summarises the results of the project, examines the different methodologies that were employed, and reviews the contribution made by action learning.